PROSESI RITUAL ADAT NGAMALO SUKU DAYAK KANAYATN DESA KELAMPAI SETOLO KABUPATEN LANDAK KALIMANTAN BARA - Sutronan, Friskatry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The Ngamalo Traditional Ritual is a hereditary practice conducted by the Dayak Kanayatn community as a prelude to planting rice seeds. It is vital to make suitable preparations in order to effectively perform the Ngamalo ceremony. Gathering the necessary tools and ingredients includes gathering kalangkakng, a pair of native hens (one female and one male), chicken eggs, poe cooked in bamboo, bontok'ng, palame, tumpi, and a machete. The current research problem is... "Prosesi Ngamalo Suku Dayak Kanayatn Kelampai Setolo Village, Landak Regency, West Kalimantan" is a descriptive research study. The descriptive research method was used in this study. The Ngamalao Traditional Ritual action is divided into two parts: the pig roba and the chicken roba. There are a total of two people involved in the use of a pig. The ritual is only attended by one person during the chicken roba parade. The Ngamalo roba ayam parade is a culturally significant event. The ngantar manta'k procession and the poroses ngantar masak procession are both part of the Traditional Ritual. The Ngamalo traditional ritual procession is notable because it is a beloved tradition and custom among the Dayak Kanayatn people. While it differs from the pig and chicken robas, they still serve the same purpose: to offer appreciation to Jubata for a successful farming operation.